Approach to infantile hemangiomas - Anil Abraham; Anupa Mary Job; Gillian Roga (Wolters Kluwer Medknow Publications, 2016)
Infantile hemangiomas are a group of vascular tumors and are considered to be one of the most common tumors in infancy. Ambiguity still prevails over its origin, etiopathogenesis, and optimal management.